Factors Associsted With Adolescent Sexual Behavior In High School Pontianak City - Kardiatun, Tutur (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2015)
Sexual behavior is any behavior that is driven by sexual desire either self-inflicted, with the opposite sex or the same sex without marriage. Sexual behavior is influenced by several factors, including : knowledge, attitudes, peers, age of first courtship, sex, frequency of meeting a boyfriend, and media information . The general objective of this research. Knowing the level of knowledge of adolescents about what factors are associated with adolescent sexual behavior of SMA in Pontianak . This study uses an observational analytic cross - sectional design. The results showed knowledge of the sexual behavior variables (p value : 0.000 < 0.005), variable attitudes toward sexual behavior(p value : 0.000 < 0.005), variable Friends risk sexual behavior (p value : 0.000 < 0.000), gender variable sexual behavior (p value : 0,0,760 > 0.005), variable frequency met girlfriend on sexual behavior (p value : 0.001 < 0.005), medium variable information on sexual behavior (p value : 0.930 > 0.005) and variable age of first courtship sexual behavior (p value : 0.202 > 0.005). Results of the above study, it was concluded that the factor of knowledge, attitudes, frequency of meeting a boyfriend, peers have been associated with sexual behavior while the age of first courtship, sex and the media does not have information on the relationship sexual behavior.